Wine and health perceptions: Exploring the impact of gender, age and ethnicity on consumer perceptions of wine and health - Kathryn J. Chang; Liz Thach; Janeen E. Olsen (Wine Economics and Policy, 2016)
This study explores U.S. wine consumers' perception of wine and health by gender, age, and ethnic background. An extensive body of epidemiological studies suggests that there are health benefits from moderate wine drinking. In light of an increased consumer preference over healthier foods and beverages, it is important to understand the health orientation of wine consumers and the effect of gender, age, or ethnicity on their perceptions of wine and health. An online survey was used to collect data from more than 1000 U.S. wine consumers. The results show that there is a statistically significant difference across demographic segments in terms of the level of health consciousness. Millennials and Asians are the most concerned, whereas Whites are the least, about health in their respective segments. Red wine is considered the healthiest wine type compared to other colors and styles. Moreover, more than 80% of the sample believes drinking red wine is healthier than drinking beer or spirits. However, nearly 50% of the sample thinks sulfites in wine can cause headaches. Managerial implications are discussed.
Keywords: 330; Demographics; Market segmentation; Wine and health